The Power of Price and Promotion: Understanding What Drives Purchases at Renjeolmies.id - Imani, Amalia Rahma; Kurniawati, Desi Tri (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Purpose –  This study aims to analyze and explain the influence of price and promotion on purchasing decisions among consumers of Renjeolmies.id   Design/methodology/approach –  This study employs an explanatory research design with a quantitative approach to examine the causal relationships between the independent and dependent variables. The study involved 131 consumers of Renjeolmies.id using a non-probability sampling method with a saturated sampling technique. Data were analyzed using multiple linear regression, supported by instrument validity and reliability tests, classical assumption tests, and statistical hypothesis testing. The hypotheses were tested using the t-test in IBM SPSS Statistics 29.   Findings – The findings indicate that both price and promotion have a positive and significant effect on purchasing decisions. These results suggest that competitive pricing strategies and effective promotional activities play an important role in encouraging consumers to purchase products from Renjeolmies.id.   Originality/value – This study provides empirical evidence on the combined role of price and promotion in shaping consumer purchasing behavior within small online culinary businesses. The findings offer practical insights for micro and small enterprises in designing effective marketing strategies to strengthen customer engagement and purchase intention in the digital marketplace.